Front Cover. Issue 10 (30th October 2018) - Maruyama, Pietro Kiyoshi; Sonne, Jesper; Vizentin‐Bugoni, Jeferson; Martín González, Ana M.; Zanata, Thais B.; Abrahamczyk, Stefan; Alarcón, Ruben; Araujo, Andréa C.; Araújo, Francielle P.; Baquero, Andrea C.; Chávez‐González, Edgar; Coelho, Aline G.; et al.
Abstract : The cover image, by Pietro Kiyoshi Maruyama et al., is based on the Research Paper Functional diversity mediates macroecological variation in plant–hummingbird interaction networks, DOI: 10.1111/geb.12776 . Photograph by Jesper Sonne.